Informal learning of primary school teachers: Considering the role of teaching experience and school culture. (April 2015) - Grosemans, Ilke; Boon, Anne; Verclairen, Christine; Dochy, Filip; Kyndt, Eva
Abstract: Teacher learning does not solely occur within formal professional development activities; in fact, the majority of learning occurs through daily practice. The current study focuses on this everyday learning and examines primary teachers' informal learning. Results showed that teachers learn through a variety of learning activities including 'experimenting', 'reflection', 'learning from others without interaction' and 'collaboration'. In addition, differences between novice and more experienced teachers were identified. More experienced teachers learn as much as their novice colleagues, however they undertake different learning activities. Finally, results reveal that although collaboration is an important source of learning, primary teachers value their autonomy. Highlights: Primary teachers undertake a variety of informal learning activities. Experimentation and collaboration are considered to be the most important activities. Experienced teachers undertake as many learning activities than novice teachers. Learning activities of novice and more experienced teachers are different. Teachers need to feel it is safe to share problems and approach colleagues.